EXAMINATION OF ACHIEVEMENT RELATIONS AND MOTIVATION OF 7th GRADE STUDENTS FOR INVOLVEMENT IN PHYSICAL EDUCATION CLASSES - Dragoljub Višnjić; Dragan Martinović; Jelena Ilić; Živorad Marković (Montenegrin Sports Academy and Faculty for Sport and Physical Education, 2010)
The relations of students achievement and motivation for involvement in PE classes were examined in a sample of 247 seventh-grade elementary school students of both sexes. The independent variables in the study were: sex, general success of the previous grade, PE grade, students' opinion on sufficiency of knowledge acquired through instruction process, students' involvement in sport. The scale for measurement of motivation consisted of 29 items obtained by adaptation of the Scale for measurement of motives of sports' achievement. Correlation analysis, multiple regression analysis and chi square test were preformed. It was established that male students manifested higher motivation that the females. The assumptions: that females will have better PE grades that the male students; that students' success was negatively related to involvement in sport; that PE grade was connected to involvement in sport; that general success was negatively related to students' involvement in PE and that PE grade is positively related to students' motivation for involvement in instruction, were not confirmed.